2015
DOI: 10.1007/s10552-015-0630-4
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic syndrome and mammographic breast density in a racially diverse and predominantly immigrant sample of women

Abstract: Purpose The metabolic syndrome (MetS, clustering of elevated blood pressure, triglycerides and glucose, reduced high-density lipoprotein cholesterol (HDL-C), abdominal obesity) has been associated with increased breast cancer risk, but less is known about its association with mammographic breast density, a strong risk factor for breast cancer. Methods We collected data on risk factors, body size and blood pressure via in-person interviews and examinations, and measured glucose, triglycerides, and HDL-C from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Participants were drawn from a sample of women who were enrolled into an ongoing observational study from a large screening mammography clinic in New York City. Of this study sample, 41 women met the eligibility criteria of self‐identifying as Hispanic and having a history of dense breasts since the enactment of NYS notification legislation, defined according to the BDN legislation (BI‐RADS density categories c and d) . Participant characteristics and risk factors were assessed at the time of enrollment (2012‐2014), which occurred on average 2.5 years prior to the qualitative interviews in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were drawn from a sample of women who were enrolled into an ongoing observational study from a large screening mammography clinic in New York City. Of this study sample, 41 women met the eligibility criteria of self‐identifying as Hispanic and having a history of dense breasts since the enactment of NYS notification legislation, defined according to the BDN legislation (BI‐RADS density categories c and d) . Participant characteristics and risk factors were assessed at the time of enrollment (2012‐2014), which occurred on average 2.5 years prior to the qualitative interviews in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…Of this study sample, 41 women met the eligibility criteria of self-identifying as Hispanic and having a history of dense breasts since the enactment of NYS notification legislation, defined according to the BDN legislation (BI-RADS density categories c and d). 11,12 Participant characteristics and risk factors were assessed at the time of enrollment (2012-2014), which occurred on average 2.5 years prior to the qualitative interviews in the current study. All participants were sent BDN as part of their clinical mammography report in English and Spanish, but none had received any information regarding breast health or breast density as part of their participation in the study.…”
Section: Study Setting and Proceduresmentioning
confidence: 99%
“…Though prior studies on statin use and MBD are limited and mixed, high blood cholesterol diagnoses (agnostic of medication use) have been inversely associated with percent density and dense area [42]. Furthermore, low blood high-density lipoprotein has been associated with greater dense area [32,43] or percent density [44,45], with some exceptions [46]. Together, these findings lend support for the hypothesis that disruption in the biological pathway involving cholesterol synthesis affected both by statin use and by the underlying disease process leading to statin prescription may be associated with MBD.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the association between medication use and MBD in the New York Mammographic Density (NY MaDe) study, an ongoing screening cohort of women, ages 40-60 years at recruitment from mammography screening appointments at a New York City facility from 2016 through 2018. This cohort has been observed to have a high prevalence of cardiometabolic risk factors [26,32]. The response rate was approximately 42%; however, the enrolled sample is socio-demographically representative of the community served by the clinic.…”
Section: Methodsmentioning
confidence: 99%
“…We used data from the Image Study, an ongoing study of mammographic density and breast cancer risk in a sample of 400 women, aged 40–64 years, who were recruited during screening mammography appointments in Northern Manhattan in New York City in 2012–2014 (Tehranifar et al, 2015). Sixty-seven percent (n=268) of Image Study participants identified as Hispanic and were included in this analysis.…”
Section: Methodsmentioning
confidence: 99%